Scratch como ferramenta de apoio a professores do ensino fundamental - Silva, Natã da Costa (2023)
This research focuses on the creation of an educational product: a teacher-training workshop titled "Scratch as a Tool to Support Elementary School Teachers," developed as a result of a study conducted within the Graduate Program in Educational Technology at the Federal University of Ceará (PPGTE-UFC). Its purpose was to empower elementary school teachers to effectively use the Scratch platform, a block-based programming tool developed by the Massachusetts Institute of Technology (MIT) that allows the creation of narratives, games, and digital animations. This was an exploratory research of a qualitative and quantitative nature carried out in two public elementary schools in Fortaleza, Ceará, involving 22 teachers. The study addressed not only the technical aspect of Scratch but also the relevance of playfulness in the teaching-learning process and how digital technology can be an important tool in this context. For the execution of the workshop, a physical workbook was created and made available digitally, along with supporting materials. The proposed training activities were in the form of Didactic Sequences, resulting in the creation of two digital educational games, ready for reproduction/adaptation, with the potential for reusing their code for new games. Before and after the training, participants responded to evaluative questionnaires, analyzed both quantitatively and qualitatively. The results highlight the ongoing relevance of teacher training and the need to incorporate technological innovations into educational practices. They also demonstrate an increase in participants' comprehension of logic and programming language concepts. A strong desire was observed among participants to apply the acquired skills in their educational practices, along with the need for creating a virtual environment where Scratch-using teachers can share experiences and knowledge, underscoring the importance of collaboration among educators. This research contributes to understanding the significance of teacher training in the digital era and illustrates how Scratch can be a valuable tool to make teaching more engaging and effective. Thus, the aim is to address the diverse needs of educators and promote an accessible and adaptable learning experience.